Sustainability and Visitor Management in Tourist Historic Cities - Lois González, Rubén Camilo; Guilarte, Yamilé; Lopez, Lucrezia (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue on 'Sustainability and Visitor Management in Tourist Historic Cities' explores new trends and methods that contribute to sustainable practices for tourism planning and management in historic cities. Thanks to the differentiated approaches adopted by the authors, the Special Issue reflects on the environmental, physical, cultural, and social effects that tourism activity provokes in tourist historic cities. Considering the present debate on tourism in historic cities, there is a special focus on resident perceptions and the social problems and conflicts associated with various tourist activities that have emerged in recent years. New methodologies and sources to measure tourism impacts are also addressed in this book, especially the use of big data technology, another relevant topic. Papers include one literature review and six case studies in the historic cities of Seville and Toledo (Spain), Venice and Matera (Italy), and Porto (Portugal) and Popayán (Colombia). This Special Issue provides practical tools and policy recommendations to measure tourism impacts and promote sustainable management in tourist historic cities.